The Effect Of Job Training And Work Experience On Performance Through Employee Motivation Of PT. Citra Indah Abadi Jaya - Lasiman; Sutomo; Handayani , Sari; Zainuddin, Ahmad; Sumunu, Trenggono (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of job training and work experience on employee performance through motivation at PT. Citra Indah Abadi Jaya. Specifically, this study examines: (1) the effect of job training on employee performance, (2) the effect of work experience on employee performance, (3) the effect of job training on performance through motivation, and (4) the effect of work experience on performance through motivation. The research population was 130 employees, with a research sample of 100 respondents obtained using the Proportional Stratified Random Sampling technique and calculations using the Slovin formula. Data analysis was carried out using the Structural Equation Modelling (SEM) method based on Partial Least Squares (PLS) with the help of SmartPLS 3 software. The results of the study show that: (1) job training has a positive and significant effect on employee performance, (2) work experience has a positive and significant effect on employee performance, (3) motivation can mediate the effect of job training on employee performance, and (4) motivation also mediates the influence of work experience on employee performance. Thus, the improvement of job training and work experience, balanced with high motivation, will have a significant impact on improving the performance of PT. Citra Indah Abadi Jaya.